Role of Manufacturing Sector and Trade, Hotel, Restaurant Sector In East Java’s Economy: Input Output Analysis - Anggari Marya Kresnowati; Candra Fajri Ananda; Moh. Khusaini (Universitas Negeri Malang, 2016)
This study aimed to (1) analyze the relationship the manufacturing sector and the trade, hotel, and restaurant sector with other sectors in East Java, (2) to analyze the economic impact caused the two sectors based on the multiplier effect, (3) and analyze the economic impact caused by these two sectors if there additional investment funds. This study uses data analysis input-output 2010 East Java 19x19 aggregation sector.The results indicate that base metals subsector has the highest linkages to other sectors. Based on household income multiplier effect, trade subsector has the greatest multiplier. Employment multiplier in trade and industrial sectors are in medium rank. This indicates that the labor has been absorbed well in both sectors. The output multiplier effect, subsector non-metal goods, except petroleum and coal has the highest multiplier. The last, according to the analysis of investment injection simulations Input-Output East Java in 2010, subsector other processing industries has a best value added. Overall, the manufacturing sector has a better influence to East Java's economy than trade, hotel, and restaurant sector.Keywords: sectoral linkages, multiplier, investment, input-output analysis, the manufacturing sector, trade hotel restaurant sectorJEL Classification: D57, 014